Impact of nanomechanical resonances on lasing from electrically pumped quantum dot micropillars - Czerniuk, T.; Tepper, J.; Akimov, A. V.; Unsleber, S.; Schneider, C.; Kamp, M.; Höfling, S.; Yakovlev, D. R.; Bayer, M. (Applied Physics Letters)
We use a picosecond acoustics technique to modulate the laser output of electrically pumped GaAs/AlAs micropillar lasers with InGaAs quantum dots. The modulation of the emission wavelength takes place on the frequencies of the nanomechanical extensional and breathing (radial) modes of the micropillars. The amplitude of the modulation for various nanomechanical modes is different for every micropillar which is explained by a various elastic contact between the micropillar walls and polymer environment.